TINDAK UJAR ILOKUSI DALAM ROMAN “UND SAGTE KEIN EINZIGES WORT” KARYA HEINRICH BӦLL - Nova Mandolang (Kadera Bahasa, 2019)
This study discusses the actions of ilokusi in the roman "Und Sagte Kein Einziges Wort" by Heinrich Böll. The focus of the research is direct and indirect illocutionary speech acts between the characters in the romance and the form of the storyteller by looking at the themes and forming elements of the romance theme. The purposes of this study are: 1) identify and describe the theme and elements forming the romance theme "Und Sagte Kein Einziges Wort"; 2) describes the form of the storyteller and the meaning of direct and indirect illocutionary acts between characters. The language approach (sprechakt) is a method of analysis applied to data based on communication in literary texts. The results of the discussion indicate that in the novel "Und Sagte Kein Einziges Wort" by Heinrich Böll there are utterances containing actions called direct ilokusi say actions which are the same as what is spoken by the speaker so that the context or situation behind the conversation is not needed to explain the meaning contained in it and the act of saying indirect illocution that requires context.